Cytoplasm-predominant Pten associates with increased region-specific brain tyrosine hydroxylase and dopamine D2 receptors in mouse model with autistic traits. Issue 1 (December 2015) - He, Xin; Thacker, Stetson; Romigh, Todd; Yu, Qi; Frazier, Thomas; Eng, Charis
Abstract Background Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders characterized by impairment in social communication/interaction and inflexible/repetitive behavior. Several lines of evidence support genetic factors as a predominant cause of ASD. Among those autism susceptibility genes that have been identified, thePTEN tumor suppressor gene, initially identified as predisposing to Cowden heritable cancer syndrome, was found to be mutated in a subset of ASD patients with extreme macrocephaly. However, the ASD-relevant molecular mechanism mediating the effect ofPTEN mutations remains elusive. Methods We developed aPten knock-in murine model to study the effects ofPten germline mutations, specifically altering subcellular localization, in ASD. Proteins were isolated from the hemispheres of the male littermates, and Western blots were performed to determine protein expression levels of tyrosine hydroxylase (TH). Immunohistochemical stains were carried out to validate the localization of TH and dopamine D2 receptors (D2R). PC12 cells ectopically expressing either wild-type or missense mutant PTEN were then compared for the differences in TH expression. Results Mice carryingPten mutations have high TH and D2R in the striatum and prefrontal cortex. They also have increased phosphorylation of cAMP response element-binding protein (CREB) and TH. Mechanistically, PTEN downregulates TH production in PC12 cells via inhibiting the phosphoinositide 3-kinase (PI3K)/CREB signaling pathway, while PTEN reduces TH phosphorylation via suppressing MAPK pathway. Unlike wild-type PTEN but similar to the mouse knock-in mutant Pten, three naturally occurring missense mutations ofPTEN that we previously identified in ASD patients, H93R, F241S, and D252G, were not able to suppress TH when overexpressed in PC12 cells. In addition, two otherPTEN missense mutations, C124S (pan phosphatase dead) and G129E (lipid phosphatase dead), failed to suppress TH when ectopically expressed in PC12 cells. Conclusions Our data reveal a non-canonical PTEN-TH pathway in the brain that may work as a core regulator of dopamine signaling, which when dysfunctional is pathogenic in ASD.